A novel analysis method for evaluating the interplay of oxygen and ionizing radiation at the gene level - Jansen, Jeannette; Vieten, Patricia; Pagliari, Francesca; Hanley, Rachel; Marafioti, Maria Grazia; Tirinato, Luca; Seco, Joao (Frontiers in genetics, 2021)
Whilst the impact of hypoxia and ionizing radiations on gene expression is well understood, the interplay of these two effects is not. To better investigate this aspect at the gene level human bladder, brain, lung and prostate cancer cell lines were irradiated with photons (6 Gy, 6 MV LINAC) in hypoxic and normoxic conditions and prepared for the whole genome analysis at 72 hours post irradiation. The analysis was performed on the obtained 20000 genes per cell line using PCA and hierarchical cluster algorithms to extract the most dominant genes altered by radiation and hypoxia. With the help of the introduced novel radiation-in-hypoxia and oxygen-impact pathways, it was possible to overcome cell line specific gene regulation patterns. Based on that, 37 genes were found to be consistently regulated over all studied cell lines. All DNA-repair related genes were down-regulated after irradiation, independently of the oxygen state. Cell cycle-dependent genes showed up-regulation consistent with an observed change in cell population in the S and G2 / M phases of the cell cycle after irradiation. Genes behaving oppositely in their regulation behaviour when changing the oxygen concentration and being irradiated, were immunoresponse and inflammation related genes. The novel analysis method and, by consequence, the results presented here have shown how it is important to consider the two effects together (oxygen and radiation) when analyzing gene response upon cancer radiation treatment. This approach might help to unrevel new gene patterns responsible for cancer radioresistance in patients.
Gesehen am 09.06.2021